Adult eyewitness testimony : current trends and developments / edited by David Frank Ross, J. Don Read, Michael P. Toglia. - Ross, David F., 1959-; Read, J. Don; Toglia, Michael P. (Cambridge University Press, 1994)
Adult Eyewitness Testimony: Current Trends and Developments provides an overview of empirical research on eyewitness testimony and identification accuracy, covering both theory and application. The volume is organized to address three important issues. First, what are the cognitive, social and physical factors that influence the accuracy of eyewitness reports? Second, how should lineups be constructed and verbal testimony be taken to improve the chances of obtaining accurate information? And third, whose testimony should be believed? Are there differences between accurate and inaccurate witnesses, and can jurors make such a distinction? Adult Eyewitness Testimony: Current Trends and Developments is crucial reading for memory researchers, as well as police officers, judges, lawyers and other members of the judicial system.